Various edge low-frequency fluctuations during transition to a detached divertor in Experimental Advanced Superconducting Tokamak. (1st June 2023) - Ding, G.F.; Chen, R.; Ye, Y.; Xu, G.S.; Wu, X.Q.; Yang, Q.Q.; Yu, L.; Meng, L.Y.; Wang, L.; Lin, X.; Wang, P.; Lan, H.
Abstract: Various edge low-frequency fluctuations with distinct characteristics exist in different detached divertor states. Three edge low-frequency fluctuations ( f < 10 kHz), namely low-frequency quasi-coherent fluctuation (LFCF), low-frequency broadband frequency fluctuation (LFBF), and low- n X-point mode (LNXM) on Experimental Advanced Superconducting Tokamak (EAST), are systematically assessed. The basic features of these fluctuations, such as spectral width, location, mode number, propagating direction, and particle transport capacities, are examined. LFCF occurs when the inner strike point is energy detached or nearly energy detached with T et, inner ∼ 8–15 eV ( T et, inner is the electron temperature of the inner strike point), and a large electron temperature gap between the inner and outer strike points with Δ T et > 25 eV ( Δ T et is the electron temperature gap between the inner and outer strike points) is essential for the occurrence of LFCF. By contrast, LFBF occurs when the inner strike point is energy detached with T et, inner < 8 eV, while the outer strike point is nearly energy detached or attached. The Δ T et of LFBF is generally lower than that of LFCF, which is < 25 eV. LNXM is related only to the radiative divertor with impurity seeding and considered to be excited by the geodesic acoustic mode proposed in earlier work (Sun 2021 Nucl. Fusion 61 014002; Diallo 2020 28th IAEA Fusion Energy Conf. ), or the coupling of impurity radiation condensation instability and drift waves proposed in a previous work (Ye 2021 Nucl. Fusion 61 116032). In addition, the possible physical mechanisms of LFBF and LFCF are proposed, with LFBF being the purely growing rippling mode and LFCF being the mode formed by the coupling of the rippling mode to the drift waves. Related research may be beneficial to better clarify the various low-frequency fluctuations that occur during different divertor states.